Enabling Creative Destruction: An Entrepreneurial Ecosystem Approach to Industrial Policy - Erik Stam (Utrecht University, Utrecht University School of Economics (U.S.E.), 2018)
Creative destruction is important for long term economic development, but hard to target with industrial policy. How to stimulate creative destruction? In this article, we set out with a critique of existing industrial policy approaches and make a plea for a "backing challengers" industry policy, which enables the creation of innovative start-ups and Schumpeterian creative destruction. This "backing challengers" policy is least likely to fall prey to the usual information and vested interest problems of industrial policy. We construct an entrepreneurial ecosystem approach to policy, which provides a synthesis of scientific insights into entrepreneurship and economic development, and a more adequate complex system perspective on the economy. We also offer diagnostics for developing policy in consultation of and collaboration with public and private stakeholders. In this way the design and implementation of policy is informed by scientific knowledge on entrepreneurial ecosystems, but also local knowledge about the context-specific bottlenecks, and involvement of the relevant stakeholders that is necessary for a successful implementation of policy.
Keywords: 330; Entrepreneurial Ecosystems; Industrial Policy; Government Failures; MarketFailures; Innovative Start-ups; Creative Destruction; Tr